Recent Advancements and Perspectives of Low-Dimensional Halide Perovskites for Visual Perception and Optoelectronic Applications - Rafique, Humaira; Abbas, Ghulam; Mendes, Manuel J.; Barquinha, Pedro; Martins, Rodrigo; Fortunato, Elvira; Águas, Hugo; Jana, Santanu (Nano-Micro Letters, 2025)
Low-dimensional (LD) halide perovskites have attracted considerable attention due to their distinctive structures and exceptional optoelectronic properties, including high absorption coefficients, extended charge carrier diffusion lengths, suppressed non-radiative recombination rates, and intense photoluminescence. A key advantage of LD perovskites is the tunability of their optical and electronic properties through the precise optimization of their structural arrangements and dimensionality. This review systematically examines recent progress in the synthesis and optoelectronic characterizations of LD perovskites, focusing on their structural, optical, and photophysical properties that underpin their versatility in diverse applications. The review further summarizes advancements in LD perovskite-based devices, including resistive memory, artificial synapses, photodetectors, light-emitting diodes, and solar cells. Finally, the challenges associated with stability, scalability, and integration, as well as future prospects, are discussed, emphasizing the potential of LD perovskites to drive breakthroughs in device efficiency and industrial applicability. Highlights: 1 This review uniquely bridges the relationship between 0D, 1D, and 2D structural motifs of halide perovskites and their distinct optoelectronic properties; such as photoluminescence, charge transport, and excitonic behavior and how these impact performance across various devices (e.g., LEDs, photodetectors, synapses). This dimensional-property-functionality mapping is not extensively covered in previous reviews. 2 Unlike many earlier reviews focused solely on photovoltaics or LEDs, this article expands into emerging fields like artificial synapses and visual perception-related electronics, offering insights into how low-dimensional perovskites could enable next-generation neuromorphic and intelligent sensing systems. 3 The review doesn't just summarize the field it also critically evaluates current limitations in scalability, environmental stability, and device integration, and provides future directions to overcome these, particularly through material design and interfacial engineering, making it highly relevant for guiding industrial research.